تعليم مهارة الاستماع باستحدام الوسيلة التعليمية السمعية البصرية الأفلام القصيرة باللغة العربية لطلاب الفصل الثاني في المدرسة المتوسطة الحكومية 8 بليتار - Aljauhari, Ahmad Khusnul Umam; Qomariyah, Lailatul (JURNAL AL-IHDA : Media Ilmiah Bahasa Arab, 2024)
Teachers need the right method so that the learning process takes place easier and more fun for students to achieve the desired learning goals. This research aims to. 1) To find out how to learn listening skills by using Arabic short film/video audio visual media for grade 8 students at Madrasah Tsanawiyah Negeri 8 Blitar. 2) Knowing the advantages and disadvantages of learning listening skills by using short Arabic film/video audio visual media for grade 8 students at Madrasah Tsanawiyah Negeri 8 Blitar. This research uses a qualitative method with a descriptive approach, and data collection techniques in the form of observation, interviews and documentation. The results of the research are: 1) In using this method, three stages are needed, namely: Teachers prepare equipment and learning implementation plans using Arabic short film/video audio visual media using LCD projectors. The teacher explains the learning objectives. The teacher explains the subject matter. 2) The advantages of the media are that it has a positive impact on students, the classroom atmosphere becomes more interactive, the educational process becomes more interesting and students become more enthusiastic and not quickly bored in following the learning process. The disadvantages of this media are that the connecting cable between the LCD and the laptop is sometimes not connected, the lack of electrical power often causes power outages, excessive lighting that affects the presentation of the material using audio-visual media.